Determinants of the Community Mobility during the COVID-19 Epidemic: The Role of Government Regulations and Information - Silvia Mendolia; Olena Stavrunova; Oleg Yerokhin (Institute of Labor Economics (IZA), 2020)
This paper studies the dynamics of human mobility during the initial stage of the COVID-19 pandemic in countries around the world. The main goal of the analysis is to empirically separate voluntary reductions in mobility driven by the information about the location-specific pandemic trends from the effects of the government-imposed social distancing mandates. Google human mobility dataset is used to track the dynamics of mobility across a wide range of categories (e.g. workplace, retail and recreational activities, etc), while information on country-specific counts of COVID-19 cases and deaths is used as a proxy for the information about the spread of the pandemic available to the population. A detailed index of stringency of the government-imposed social distancing policies in around 100 countries is used as a measure of government response. We find that human mobility does respond in a significant way to the information about the spread of the pandemic. This channel can explain about 14% of the overall reduction in mobility across the affected countries. At the same time, our results imply that government-imposed policies account for the majority of the reduction in the mobility observed during this period.
Keywords: H12; D70; I18; D80; 330; COVID-19; mobility; government response; information; group fixed effects